Eksistensi Covernote dan Pertanggungjawaban Notaris dalam Penerbitannya: Studi Kasus Putusan Mahkamah Agung Nomor 1673 PK/Pid.Sus/2024 - Hasibuan, Andika; Syahrin, Alvi; Siahaan, Rudy Haposan (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study examines the practice of notary covernote issuance in banking transactions in Indonesia, focusing on the case in Supreme Court Decision Number 1673 PK/Pid.Sus/2024. Although not explicitly regulated in UUJN, covernote has developed as a living law in banking practice. The case of Notary E is in the spotlight because the issuance of a covernote that is not in accordance with the facts caused bad debt and state losses, with the verdict experiencing dynamics from the Medan District Court to the Judicial Review, which finally determined a sentence of 2 years and 8 months considering the defendant's role as an assistant and not gaining direct benefits.